An inhibitor-mediated beta-cell dedifferentiation model reveals distinct roles for FoxO1 in glucagon repression and insulin maturation - Tamara Casteels; Yufeng Zhang; Thomas Frogne; Caterina Sturtzel; Charles-Hugues Lardeau; Ilke Sen; Xiaocheng Liu; Shangyu Hong; Florian M. Pauler; Thomas Penz; Marlene Brandstetter; Charlotte Barbieux; et al. (Elsevier, 2021)
Objective: The loss of forkhead box protein O1 (FoxO1) signaling in response to metabolic stress contributes to the etiology of type II diabetes, causing the dedifferentiation of pancreatic beta cells to a cell type reminiscent of endocrine progenitors. Lack of methods to easily model this process in vitro, however, have hindered progress into the identification of key downstream targets and potential inhibitors. We therefore aimed to establish such an in vitro cellular dedifferentiation model and apply it to identify novel agents involved in the maintenance of beta-cell identity. Methods: The murine beta-cell line, Min6, was used for primary experiments and high-content screening. Screens encompassed a library of small-molecule drugs representing the chemical and target space of all FDA-approved small molecules with an automated immunofluorescence readout. Validation experiments were performed in a murine alpha-cell line as well as in primary murine and human diabetic islets. Developmental effects were studied in zebrafish and C. elegans models, while diabetic db/db mouse models were used to elucidate global glucose metabolism outcomes. Results: We show that short-term pharmacological FoxO1 inhibition can model beta-cell dedifferentiation by downregulating beta-cell-specific transcription factors, resulting in the aberrant expression of progenitor genes and the alpha-cell marker glucagon. From a high-content screen, we identified loperamide as a small molecule that can prevent FoxO inhibitor-induced glucagon expression and further stimulate insulin protein processing and secretion by altering calcium levels, intracellular pH, and FoxO1 localization. Conclusions: Our study provides novel models, molecular targets, and drug candidates for studying and preventing beta-cell dedifferentiation.